The role of green and sustainability offices in fostering sustainability efforts at higher education institutions - Walter Leal and Markus Will and Amanda Lange Salvia and Maik Adomßent and Anselm Grahl and Felix Spira (Journal of Cleaner Production, 2019)
Green and Sustainability Offices are special settings which assist initiatives within higher education institutions to coordinate their efforts and work in the field of sustainable development. The set-up of such offices is known to be an effective tool in supporting the implementation of sustainability initiatives on campuses, and in fostering awareness among students and staff on matters related to sustainable development. But despite their usefulness and proven effectiveness, the use of Green Offices and Sustainability Offices is not as wide as it could -or should-be. Also, there is a limited amount of empirical international work performed to date, which have investigated the various barriers related to their works. This paper, which focus on the role played by green offices in a higher education context, addresses a research gap. On the basis of the need to address this research gap, this paper presents the results of an international study on Green and Sustainability Offices, performed with a sample of 70 higher education institutions from round the world. The study consisted of an on-line survey which identified the extent to which Green Offices or similar governance structures are being deployed, some specific aspects of their operations and the barriers or difficulties related to their activities. The study concludes by suggesting some topics higher education institutions may take into consideration, in order to maximise their potential benefits.
Keywords: Sustainability management at universities; Green offices